Meshless finite element method: using non-uniform rational B-splines - Sheng, Ni. (2008)
To alleviate the major difficulties in the prevailing mashes methods, a research program was initiated to propose a robust alternative for solving a broad class of boundary-value problems. In this program, Non-Uniform Rational B-Spline (NURBS) basis functions are used directly to construct the approximation function.